Media Representation of Women Politicians from a Gender to an Intersectionality Perspective - Christina Fiig (The Royal Danish Library, 2010)
Media Representations of Women Politi- cians from a Gender to an Intersectionality Perspective. This article investigates media representation from a perspective of intersectionality defined as one that deconstructs the category ‘woman’ by looking at different social divisions such as class, ethnicity, gender, race and sexuality. An intersectionality perspective is constructive in broadening the debate on the media as a powerful political site for different groups of men and women politicians. The analytical point of the article is that a perspective of intersectionality deepens the understanding of the ways that the media organize power through stereotypical representation and homogenization of social categories.